The Role of the Human Factor in Digital Management - Jasmina, Samadova; Tillaoy, Rakhmonova (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
This article highlights the role and importance of the human factor in digital governance processes. As digital technologies penetrate all spheres of life, new opportunities are emerging in management systems as well. However, the effective functioning of digital systems largely depends on the level of human knowledge, skills, and responsibility. The article discusses the development of human capital, the improvement of digital literacy, and the role of humans in managing modern technologies. In addition, it analyzes the reforms being implemented in Uzbekistan to develop digital governance and strengthen the human factor within this process.